Lumales - Mawuntu, Marhaeni; Tumiwa, Jever Kivri; Runtuwene, Hendry M. C. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
This research explores the tradition of Lumales (stepping in noble trails) as a medium for Minahasa tou to now understand the concept of omnipresent divinity in local traditions. At the same time, it dismisses the misunderstanding that local traditions do not have an element of God's omnipresence. This research will explore the experiences of the ancestors with the Holy One, the Omniscient God, through all the paths of life they have built. Furthermore, the exploration carried out on Lumales cultural activities will use a qualitative research approach combined with an ethnographic approach. This research will depart from oral data that is transmitted and is still maintained among cultural actors and Minahasa people in several villages. Furthermore, based on such an approach, the author will offer Lumales: Experiencing God Omnnipresent in the cultural activities of Tou Minahasa Christianity now as a theology based on the local Minahasa narrative.